Comparison of the Concept of Maslahah in the Thought of At-Thufi and Al-Syathibi and its Relevance in Islamic Law - Ayu Juniaty Siregar; Rina Solin (AT-TAFAHUM: Journal of Law, 2024)
This study discusses the comparative concept of maslahah in the thoughts of Najm al-Din al-Tufi (At-Thufi) and Abu Ishaq al-Syathibi and its relevance in the development of Islamic law. Maslahah as an important principle in ushul fiqh has a strategic role in establishing laws that are in accordance with human needs and changes in shari'a. At-Thufi tends to give a strong position to maslahah, even in certain conditions it can be prioritized over dzanni texts, especially in the realm of muamalah. Meanwhile, Al-Syathibi places maslahah as the main objective of sharia (maqasid al-shari'ah) which must remain within the corridor of the text and not contradict the qath'i argument. This study uses a qualitative method with a library research approach through analysis of classical and contemporary ushul fiqh literature. The results of the study show differences in epistemological approaches between the two, but both emphasize that maslahah is the core of the objectives of sharia. The relevance of both of their thoughts is very important in answering the dynamic and complex issues of contemporary Islamic law.